Cancer-Specific Delivery of Proteolysis-Targeting Chimeras (PROTACs) and Their Application to Cancer Immunotherapy - Moon, Yujeong; Jeon, Seong Ik; Shim, Man Kyu; Kim, Kwangmeyung (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Proteolysis-targeting chimeras (PROTACs) are rapidly emerging as a potential therapeutic strategy for cancer therapy by inducing the degradation of tumor-overexpressing oncogenic proteins. They can specifically catalyze the degradation of target oncogenic proteins by recruiting E3 ligases and utilizing the ubiquitin-proteasome pathway. Since their mode of action is universal, irreversible, recyclable, long-lasting, and applicable to 'undruggable' proteins, PROTACs are gradually replacing the role of conventional small molecular inhibitors. Moreover, their application areas are being expanded to cancer immunotherapy as various types of oncogenic proteins that are involved in immunosuppressive tumor microenvironments. However, poor water solubility and low cell permeability considerably restrict the pharmacokinetic (PK) property, which necessitates the use of appropriate delivery systems for cancer immunotherapy. In this review, the general characteristics, developmental status, and PK of PROTACs are first briefly covered. Next, recent studies on the application of various types of passive or active targeting delivery systems for PROTACs are introduced, and their effects on the PK and tumor-targeting ability of PROTACs are described. Finally, recent drug delivery systems of PROTACs for cancer immunotherapy are summarized. The adoption of an adequate delivery system for PROTAC is expected to accelerate the clinical translation of PROTACs, as well as improve its efficacy for cancer therapy.